Fatigue self‐management: a survey of Chinese cancer patients undergoing chemotherapy. Issue 7 (11th March 2013) - Lou, Yan; Yates, Patsy; McCarthy, Alexandra; Wang, HeMei
<x xml:space="preserve">Abstract</x> Aims and objectives To examine Chinese cancer patients' fatigue self‐management, including the types of self‐management behaviours used, their confidence in using these behaviours, the degree of relief obtained and the factors associated with patients' use of fatigue self‐management behaviours. Background Fatigue places significant burden on patients with cancer undergoing chemotherapy. While some studies have explored fatigue self‐management in Western settings, very few studies have explored self‐management behaviours in China. Design Cross‐sectional self‐ and/or interviewer‐administered survey. Methods A total of 271 participants with self‐reported fatigue in the past week were recruited from a specialist cancer hospital in south‐east China. Participants completed measures assessing the use of fatigue self‐management behaviours, corresponding self‐efficacy, perceived relief levels plus items assessing demographic characteristics, fatigue experiences, distress and social support. Results A mean of 4·94 (±2·07; range 1–10) fatigue self‐management behaviours was reported. Most behaviours were rated as providing moderate relief and were implemented with moderate self‐efficacy. Regression analyses identified that having more support from one's neighbourhood and better functional status predicted the use of a greater number of self‐management behaviours. Separate regression analyses identified that greater neighbourhood support predicted greater relief from 'activity enhancement behaviours' and that better functional status predicted greater relief from 'rest and sleep behaviours'. Higher self‐efficacy scores predicted greater relief from corresponding behaviours. Conclusions A range of fatigue self‐management behaviours were initiated by Chinese patients with cancer. Individual, condition and environmental factors were found to influence engagement in and relief from fatigue self‐management behaviours. Relevance to clinical practice Findings highlight the need for nurses to explore patients' use of fatigue self‐management behaviours and the effectiveness of these behaviours in reducing fatigue. Interventions that improve patients' self‐efficacy and neighbourhood supports have the potential to improve outcomes from fatigue self‐management behaviours.